2013
DOI: 10.1002/mds.25679
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia—an independent risk factor for impulsive‐compulsive disorders in Parkinson's disease

Abstract: Impulsive-compulsive disorders (ICDs) are frequent side effects of dopaminergic medication in Parkinson's disease (PD). Alexithymia, a personality trait characterized by difficulties identifying and describing feelings and an externally oriented thinking style, has been linked to various impulse-control problems in the general population. In PD, the prevalence of alexithymia is approximately twice as high as in the general population. However, whether alexithymia is associated with ICDs in PD is currently unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 36 publications
8
33
0
1
Order By: Relevance
“…Similarly high (>30%) prevalence rates have been reported in other studies using the QUIP-RS (Papay et al, 2011;Lim et al, 2011;Goerlich-Dobre et al, 2014). Given that the diagnosed prevalence of ICDs in the current study was close to that reported elsewhere (11.1%), the greater level of selfreported ICDs supports the theory that ICDs are under reported and often may not always be recognised by clinicians (Vilas et al, 2011;Voon & Fox, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly high (>30%) prevalence rates have been reported in other studies using the QUIP-RS (Papay et al, 2011;Lim et al, 2011;Goerlich-Dobre et al, 2014). Given that the diagnosed prevalence of ICDs in the current study was close to that reported elsewhere (11.1%), the greater level of selfreported ICDs supports the theory that ICDs are under reported and often may not always be recognised by clinicians (Vilas et al, 2011;Voon & Fox, 2007).…”
Section: Discussionsupporting
confidence: 88%
“…12 Another cause of underreporting might be deliberate withholding of relevant information due to the often humiliating nature of these symptoms. In this line, Farnikova and colleagues examined personality characteristics in PD patients with and without ICD.…”
Section: Discussionmentioning
confidence: 99%
“…Further, few studies have investigated the prevalence and predictors of ICDs. For example, it was reported that alexithymia is a predictor of ICDs in PD patients (Goerlich-Dobre et al, 2013). It was also found that frontal executive function is a predictor of the occurrence of pathological gambling (Santangelo et al, 2009b).…”
Section: Impulse Control Disorders In Pdmentioning
confidence: 99%